2005
DOI: 10.1037/0893-3200.19.2.252
|View full text |Cite
|
Sign up to set email alerts
|

Parent and Peer Predictors of Physical Aggression and Conflict Management in Romantic Relationships in Early Adulthood.

Abstract: Violence between romantic partners is widespread, but developmental precursors of perpetration and victimization are little understood. Among participants followed from birth to 23 years of age, familial and extrafamilial childhood and adolescent relationships were examined in connection with couple violence in early adulthood. Predictors included early childhood physical abuse and witnessing of parental partner violence, features of parent-child interactions at the age of 13 years, and close friendship qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
170
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(187 citation statements)
references
References 64 publications
(70 reference statements)
15
170
2
Order By: Relevance
“…It is also important to note that the predictors identified in various studies from Pakistan are not unique to Pakistan and have been reported in studies from other countries as well (Capaldi, Knoble, Shortt, & Kim, 2012). For instance, childhood abuse and witnessing IPV as a child (Ehrensaft et al, 2003;Linder & Collins, 2005;Roberts, Gilman, Fitzmaurice, Decker, & Koenen, 2010), aggressive nature (Moffitt, Krueger, Caspi, & Fagan, 2000) and unemployment (Brownridge & Halli, 2002;Caetano, Vaeth, & Ramisetty-Mikler, 2008;Capaldi et al, 2012;Ellison, Trinitapoli, Anderson, & Johnson, 2007). Similarly, effects of IPV identified in this review are consistent with reported effects of IPV in studies from other countries (Dillon, Hussain, Loxton, & Rahman, 2013;Vives-Cases, Ruiz-Cantero, Escribà-Agüir, & Miralles, 2011;WHO, 2010).…”
Section: Discussionsupporting
confidence: 74%
“…It is also important to note that the predictors identified in various studies from Pakistan are not unique to Pakistan and have been reported in studies from other countries as well (Capaldi, Knoble, Shortt, & Kim, 2012). For instance, childhood abuse and witnessing IPV as a child (Ehrensaft et al, 2003;Linder & Collins, 2005;Roberts, Gilman, Fitzmaurice, Decker, & Koenen, 2010), aggressive nature (Moffitt, Krueger, Caspi, & Fagan, 2000) and unemployment (Brownridge & Halli, 2002;Caetano, Vaeth, & Ramisetty-Mikler, 2008;Capaldi et al, 2012;Ellison, Trinitapoli, Anderson, & Johnson, 2007). Similarly, effects of IPV identified in this review are consistent with reported effects of IPV in studies from other countries (Dillon, Hussain, Loxton, & Rahman, 2013;Vives-Cases, Ruiz-Cantero, Escribà-Agüir, & Miralles, 2011;WHO, 2010).…”
Section: Discussionsupporting
confidence: 74%
“…Male children who witness IPV are more likely to use IPV in adulthood (Roberts, A., et.al. 2010) and children who were abused are more likely to use IPV in early adulthood (Linder and Collins, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Those that witness IPV and a pattern of substance abuse may be prone to replicate the paternal pattern (Roberts, A., et.al. 2010;Linder and Collins, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Individual level factors include youth substance use (O'Donnell et al 2006;Reyes et al 2012), sexual risk behaviors (Cleveland et al 2003), poor emotion regulation (Foshee et al 2010), and acceptance of traditional gender roles (Lichter and McCloskey 2004). Relationship-level factors include conflict in dating relationships (Connolly et al 2010), parental modeling of conflict (Stocker and Richmond 2007), peers experiencing and perpetrating peer and/or dating violence (Foshee et al 2010), and negative parent-child interactions (Ehrensaft and Cohen 2012;Linder and Collins 2005).…”
mentioning
confidence: 99%